Esthetic of the Gabone's novel? : realism and oral tradition - (:unkn) unknown (My University, 2005)
The esthetic nature of the novel of Gabon is marked by two major influences : Realism and Oral tradition. Realism is firstly rooted in the geography and culture of the people. Looked at through the lens of "power" - we first see the influence of "political power" found in African literature since the period of independence in the 1960's, and from another angle that of "witchcraft" a recurrent theme in particular in Gabon novel. The recording of oral traditions is birthed from a place of "realism" with writers describing village life through the beliefs and rituals of the people. The place of "oral tradition" in the novel of Gabon is the second part of this study. "Oral tradition" encompasses all the rich wisdom of a people, transferred from ear to ear, from past generations through the ages. The transposition of "oral tradition" in the literature is a recording of the African oral universe made up of its beliefs and practices. There is from one side the desire to convey the traditions of a people, and from the other side, to expose the shortcoming of modern society. In the third part of this study, there is under-line through the ties between political power and witchcraft, a calling into question of traditional practices in modern society. Literature serves as a tool to analyse society, with some authors opting for a "hidden" denunciation through the use of writing styles, which offer a certain "security", especially during periods where it is not advisable to criticize the actions of political power. Others denounce through the depiction of "truth" or modern reality. The rehabilitation of society needs therefore to pass through the use of words that are forever a part of ancestral wisdom.
Keywords: African Research